Sensitivity and reproducibility of a fatigue response in elite youth football players - Fitzpatrick, J. F.; Akenhead, R.; Russell, M. R.; Hicks, K. M.; Hayes, P. R. (Science and Medicine in Football, 2019)
Objective:This study aimed to establish firstly, the sensitivity of subjective wellness, jump performance and triaxial accelerometer measures to training-induced fatigue and secondly, the reproducibility of this training-induced fatigue response. Methods: In 14 elite youth football players, morning assessments of subjective wellness (fatigue, sleep quality, muscle soreness, stress and mood), jump performance (countermovement jump height [CMJ], squat jump height [SJ] and drop jump contact time [DJ-CT], height [DJ-JH] and reactive strength index [DJ-RSI]) and triaxial accelerometer data (PlayerLoadTM (PL), the individual movement planes of PL (anterior-posterior [PLAP], mediolateral [PLML] and vertical [PLV]) and the percentage contribution of each component plane) were collected before (-24 h and immediately prior) and after (+24 h, +48 h) a standardised strenuous training session on two occasions in order to assess the reproducibility of a training-induced fatigue response. Sensitivity was assessed via the signal: noise (S:N) ratio of the changes in fatigue measures +24 h post training and the minimum detectable change for each measure. Results: DJ-RSI, PLML and %PLV were found to be sensitive measures of training-induced fatigue, which displayed a reproducible response (S:N > 1 on both occasions). CMJ, SJ and all subjective wellness measures were not able to detect a reproducible fatigue response.